Environmental hydrology - Ward, Andy D.; Trimble, Stanley Wayne ;Burckhard, Suzette Renae ;Lyon, John G (Boca Raton, Florida : CRC Press, 2016)
The late Professor Reds Wolman in his Foreword to the award-winning second edition said, "This is not your ordinary textbook. Environmental Hydrology is indeed a textbook, but five elements often found separately combine here in one text to make it different. It is eclectic, practical, in places a handbook, a guide to fieldwork, engagingly personal and occasionally opinionated. $1! = (Band, perhaps most engaging to me, in places the authors offer personal views as well as more strongly worded opinions. The former often relate to evaluation of alternative approaches, or formulations, of specific solutions to specific hydrologic problems."s
The hydrologic cycle, water resources, and society -- Precipitation -- Infiltration and soil water processes -- Soil moisture and evapotranspiration -- Runoff and drainage -- Stream processes -- Uniform open channel flow -- Hydraulic control structures -- Soil conservation and sediment budgets -- Hydrology of forests, wetlands, and cold climates -- Hydrogeology -- Human impacts on water resources : prevention and treatment strategies -- Fundamentals of remote sensing and geographic information systems for hydrologic applications -- Practical exercises on conducting and reporting hydrologic studies.
Includes bibliographical references and index.
Keywords: HYDROLOGY